1993
DOI: 10.1088/0256-307x/10/4/015
|View full text |Cite
|
Sign up to set email alerts
|

Multi-photon Up-conversion Luminescence of ErP 5 O 14 Noncrystalline

Abstract: In this paycr we report the observation of multi-photon up-conversion luininescence phenomenon of ErPS014 noncrystalline induced by pulse DCAI dye laser and clarifjg that ihe mechanism of up-conversion is the step t).v step ahsorption of single E?+ ion.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
5
0

Year Published

1999
1999
2017
2017

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 3 publications
0
5
0
Order By: Relevance
“…Studies of the upconversion luminescence in Er/Yb codoped phosphate glass will allow greater understanding of the energy transfer and transition mechanisms in these materials and may prove beneficial in the development of short wavelength ͑e.g., green͒ lasers. Chen et al 3 have studied the upconversion luminescence of erbium-doped phosphate glass excited by a dye laser. Lu et al 4,5 reported the upconversion luminescence of erbium-doped phosphate glass and fiber excited by Nd:YAG laser.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Studies of the upconversion luminescence in Er/Yb codoped phosphate glass will allow greater understanding of the energy transfer and transition mechanisms in these materials and may prove beneficial in the development of short wavelength ͑e.g., green͒ lasers. Chen et al 3 have studied the upconversion luminescence of erbium-doped phosphate glass excited by a dye laser. Lu et al 4,5 reported the upconversion luminescence of erbium-doped phosphate glass and fiber excited by Nd:YAG laser.…”
mentioning
confidence: 99%
“…7,8 Usually only the two-photon upconversion processes are observed, and the mechanism of these two-photon transitions has been extensively analyzed in Er/Yb-codoped materials. [3][4][5]9 In this letter, we present the three-photon upconversion process in Er/Yb codoped phosphate glass. Our efforts have focused on measurement and characterization of the three-photon upconversion process in Er/Yb codoped phosphate glass.…”
mentioning
confidence: 99%
“…In recent years, luminescence materials doped with Dy 3+ have attracted broad attention due to its white emission under vacuum ultraviolet excitation [1][2][3][4] . As a rule, Dy 3+ has two prominent bands in the emission spectra in many host matrixes.…”
Section: Introductionmentioning
confidence: 99%
“…Rare-earth-ions-doped phosphate-based luminescence materials have been applied in various fields, such as colour televisions, mercury-free fluorescence lamp and visible light [1][2][3][4][5] . So it can be inferred that orthophosphates are potential host crystal for its application in vacuum ultraviolet range 6,7 .…”
Section: Introductionmentioning
confidence: 99%
“…Many efforts have been made to discover host materials as well as activators with high performance [1][2][3]. Recently, germanates have attracted much attention and have been widely investigated as new host materials for light emitting devices (1) For application in FEDs, Xiao et al [4] and Minami et al [5] have reported the (Zn 2 SiO 4 )-(Zn 2 GeO 4 ):Mn 2 þ as an efficient phosphor.…”
Section: Introductionmentioning
confidence: 99%